Shakespearean Tragedy and Gender - Sprengnether, Madelon; Garner, Shirley Nelson, 1935- (Book collections on Project MUSE., 1996)
"Shakespeare is not our contemporary, the contributors to Shakespearean Tragedy and Gender emphatically conclude--yet coping with his cultural influence is never a simple matter. Ranging from Shakespeare's earliest attempts at tragedy in Richard III and Titus Andronicus, this volume covers the major tragic period, giving special attention to Othello"--Back cover.